Gifted Program Evaluation: Catalyst for Change or Keeper of the Culture. Issue 4 (October 2019) - Robbins, Janice I.
This article presents a view of barriers to effective gifted program evaluation resulting from ineffective tools for measuring growth in gifted students and the human barriers confounding the evaluation process. The role of advocacy in the design, implementation, and utilization of evaluation studies is examined. Long held beliefs and biases related to gifted education are recognized as influencing program evaluations. The recognition of the strengths and challenges inherent in the educational role of specific stakeholder groups is presented. Suggestions for developing an emerging cadre of advocates for gifted education are detailed.